The Effect of Teaching Factory, Industrial Work Practices and Vocational Competence Through Self-Efficacy on Work Readiness of Vocational High School Students - Mega Amelia Prihatini Hatta; Fahmi Rizal; Rahmiati Rahmiati; Yeka Hendriyani (JETL (Journal of Education, Teaching and Learning), 2025)
This study aims to examine the effect of Teaching Factory (TeFa), Industrial Work Practices (Prakerin), and vocational competence on students' work readiness, with self-efficacy as a mediator. The method used is Systematic Literature Review (SLR), which collects and synthesizes various studies related to learners' work readiness, focusing on variables that play a role in vocational education. The findings show that Teaching Factory and Prakerin have an important role in improving learners' technical and non-technical skills, as well as bridging the gap between academic learning and industry needs. Self-efficacy was found to be a factor that strengthens learners' confidence and performance in the industrial environment. This study concludes that holistic development of technical competencies, work-based experiences, and strengthening self-efficacy can improve learners' readiness to face the challenges of the world of work. Further research needs to focus on the long-term impact of these programs as well as the role of teachers in facilitating industry-based learning